Clonality of chronic neutrophilic leukaemia associated with myeloma: analysis using the X-linked probe M27 beta. - Standen, G R (1993)
AIMS--To determine whether myeloid proliferation was monoclonal or polyclonal in a woman with chronic neutrophilic leukaemia and myeloma. METHODS--The X-linked probe, M27 beta was used to determine the clonality of the neutrophil population by analysis of restriction fragment length polymorphisms and X inactivation pattern. RESULTS--A polyclonal pattern of X inactivation was obtained for the neutrophil population in this patient. CONCLUSION--The myeloid expansion in chronic neutrophilic leukaemia associated with myeloma represents a polyclonal reactive response to the plasma cell clone rather than a co-existent myeloproliferative disorder.